Enhancing the Technique of Eye Drop Administration through Evaluation and Education: A Quality Improvement Initiative: Doi: 10.36351/pjo.v40i2.1734 - Saif, Marwa; Shabbeer, Fatima; Ilyas, Hareem; Saif, Safa; Imtiaz, Usman (Pakistan Journal of Ophthalmology, 2024)
Purpose: To evaluate the eye-drop administration technique and see the effect of education in improving the eye drop delivery method. Study Design: Interventional case series. Place and Duration of Study: Central Park Teaching Hospital Lahore from May-2022 to September-2022 Methods: This study includes 341 patients who had been self-administering eye drops as a treatment for glaucomaor any other disorder. The patients were asked to instill the drop by using a 5ml Systane bottle, as they should do at home. Two observers assessed the technique. Patients were educated about the techniques and they were re-assessed in the form of a post-test. They were evaluated by the same observers again. Data was analyzed suing Fisher’s Exact test. Results: A significant improvement was observed in several parameters, including the mean time (in seconds) taken to instill the first drop, the number of drops squeezed, the number of drops reaching the conjunctival sac at the first attempt, hand washing, shaking the bottle before instillation, tilting the head backwards during drop instillation, and the occurrence of drops falling on the cheek (p ≤ 0.05). Conversely, statistically insignificant improvements were noted in parameters such as touching the tip of the dropper and closing the eye for a minute. Conclusion: The findings underscore the importance of enhancing patient education regarding the correct technique for drop instillation.